Electromagnetic wave shield film

The electromagnetic shielding film with a laminated or impregnated carbon nanotube nonwoven fabric structure addresses the dispersion and handling issues of carbon nanotubes, providing effective electromagnetic shielding across a broad frequency range and ease of use.

JP2025002842AActive Publication Date: 2025-01-09SHIN ETSU CHEMICAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023103209
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09
Estimated Expiration
2043-06-23

AI Technical Summary

Technical Problem

Carbon nanotubes, due to their fine fiber form, have a large specific surface area and cannot be dispersed in large quantities in resin, leading to insufficient electrical conductivity and handling difficulties in existing electromagnetic shielding materials.

Method used

An electromagnetic shielding film is developed with a laminated or impregnated structure using carbon nanotube nonwoven fabric, laminated with resin films or impregnated with resin, and featuring a release film via an adhesive layer, achieving a specific resistance of 0.005Ω·cm or less and a thickness of 500μm or less, with a vertical/horizontal tensile strength ratio of 0.5 to 2.0.

Benefits of technology

The film effectively shields electromagnetic waves across a wide frequency range from low to high frequencies, is easy to handle, and maintains excellent electromagnetic shielding properties while being lightweight and flexible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002842000001_ABST
    Figure 2025002842000001_ABST
Patent Text Reader

Abstract

To provide an electromagnetic wave shield film that covers an electronic component and a wire, mounted to an internal part of an electron device that can sufficiently exert a characteristic as an electromagnetic wave shield member by a carbon nano tube, and can be easily handled.SOLUTION: In a first electromagnetic wave shield film 1a having a five-layer structure, a resin film 3 where a specific resistance is 0.005 Ω*cm or less; a thickness is 500 μm or less; a direction where a tension strength becomes the maximum is a vertical direction; and a tension strength ratio of the vertical direction / a lateral direction where a direction vertical to the vertical direction is the lateral direction is 0.5 to 2.0 is laminated onto front and back surfaces of a carbon nanotube nonwoven fabric 2, and the first electromagnetic wave shield film has a lamination film having a total thickness of 10 to 1000 μm or an impregnation film in which a resin is impregnated into the carbon nanotube nonwoven fabric, and which has a total thickness of 10 to 1000 μm, an adhesive agent layer 4 laminated onto one surface of the lamination film or the impregnation film, and a separation type film 5 laminated onto an adhesive surface of the adhesive agent layer.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electromagnetic wave shielding film that covers electronic components and wiring mounted inside an electronic device to block electromagnetic waves. [Background technology]

[0002] In recent years, high-speed communications such as 5G and 6G that use millimeter-wave and terahertz-wave electromagnetic waves are being considered for future practical use. Wireless devices that use electromagnetic waves for communication are increasing, and the ever-increasing electromagnetic waves pose the risk of electronic devices malfunctioning due to interference from electromagnetic waves from the surroundings, and the risk of information leakage due to electromagnetic waves emitted by the electronic devices themselves. In addition, in order to promote the rapid development of autonomous driving such as automobiles, it is necessary to properly transmit and receive electromagnetic waves in various electromagnetic environments, from low-frequency electromagnetic waves to millimeter-wave radar.

[0003] In order to avoid such electromagnetic interference, electromagnetic wave shielding has become an important technical issue. In this context, there is a demand for electromagnetic wave shielding materials with excellent electromagnetic wave shielding performance in the microwave, millimeter wave, and terahertz wave bands. As the use of electromagnetic waves becomes more advanced, there is also a growing need for new functionality in electromagnetic wave shielding materials, such as thinner films, lighter weight, and larger areas.

[0004] In addition to metal materials, many electromagnetic wave shielding technologies have been proposed using conductive polymers, dielectric oxides, etc., such as carbon black, graphene, and carbon nanotubes, as electromagnetic wave shielding materials. Among these, carbon nanotubes made of carbon are attracting attention as a promising electromagnetic wave shielding material.

[0005] Electromagnetic wave shielding materials using carbon nanotubes include a paste material in which carbon nanotubes are dispersed in a resin (Patent Document 1) and a water-based paint in which carbon nanotubes are dispersed in an aqueous solution (Patent Document 2), but both are difficult to handle and do not have sufficient shielding performance to be practical.The carbon nanotubes used are also in the form of fine fibers, so they have a large specific surface area and cannot be dispersed in large quantities in resin, and therefore their electrical conductivity is insufficient. In addition, there is an electromagnetic wave shielding material (Patent Document 3) that uses a carbon nanotube sheet formed by electrospinning, but it has problems such as low strength and difficulty in handling.

[0006] An electromagnetic wave shielding material (Patent Document 4) has been disclosed in which a protonating agent such as hydronium ions or hydrochloric acid is added to a sheet of carbon nanotubes, and then ferromagnetic materials such as iron or cobalt are added to improve conductivity; however, the protonating agent is a strongly acidic compound, and handling it is problematic. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2009-144000 A [Patent Document 2] JP 2012-174833 A [Patent Document 3] JP 2008-218859 A [Patent Document 4] Patent No. 6182176 Summary of the Invention [Problem to be solved by the invention]

[0008] Carbon nanotubes, which are made from carbon, have been attracting attention as an electromagnetic wave shielding material. However, because carbon nanotubes are in the form of fine fibers, their specific surface area is large and they cannot be dispersed in large quantities in resins, so the properties of the carbon nanotube electromagnetic wave shielding material are not fully utilized.

[0009] An object of the present invention is to provide an electromagnetic wave shielding film that can fully exhibit the properties of an electromagnetic wave shielding material made of carbon nanotubes and is easy to handle, and that covers electronic components and wiring mounted inside electronic devices. [Means for solving the problem]

[0010] In view of the above circumstances, the present inventors have conducted intensive research and have found that the following electromagnetic wave shielding film achieves the above object, thereby completing the present invention. That is, the present invention provides the following electromagnetic wave shielding film. [1] a carbon nanotube nonwoven fabric having a resistivity of 0.005 Ω cm or less, a thickness of 500 μm or less, and a longitudinal / lateral tensile strength ratio of 0.5 to 2.0, with the longitudinal direction being the direction in which the tensile strength is greatest and the transverse direction being the direction perpendicular to the longitudinal direction, being 0.5 to 2.0; and a laminated film having a total thickness of 10 to 1000 μm, the laminated film being obtained by laminating a resin film on both sides of the carbon nanotube nonwoven fabric. A pressure-sensitive adhesive layer laminated on one surface of the laminate film; and a release film laminated on the adhesive surface of the adhesive layer. [2] an impregnated film having a total thickness of 10 to 1000 μm, which is obtained by impregnating a carbon nanotube nonwoven fabric with a resin, the carbon nanotube nonwoven fabric having a resistivity of 0.005 Ω cm or less, a thickness of 500 μm or less, and a longitudinal / lateral tensile strength ratio of 0.5 to 2.0, where the longitudinal direction is the direction in which the tensile strength is greatest and the transverse direction is the direction perpendicular to the longitudinal direction; a pressure-sensitive adhesive layer laminated on one surface of the impregnated film; and a release film laminated on the adhesive surface of the adhesive layer. [3] The electromagnetic wave shielding film according to [1] or [2], wherein the carbon nanotubes in the carbon nanotube nonwoven fabric are single-walled carbon nanotubes, multi-walled carbon nanotubes, or a mixture thereof. [4] The electromagnetic wave shielding film according to [1], wherein the resin film is a thermoplastic resin film, and the softening point of the thermoplastic resin in the film is 400° C. or lower. [5] The electromagnetic wave shielding film according to [4], wherein the thermoplastic resin in the thermoplastic resin film contains one or more selected from polyethylene, polypropylene, fluororesin, polyethylene terephthalate, polyethylene naphthalate, and polyimide. [6] The electromagnetic wave shielding film according to [1], wherein the resin film is a thermosetting resin film, and the thermosetting resin in the film contains one or more types selected from epoxy resins, allylated epoxy resins, allylated polyphenylene ether resins, phenolic resins, polyimide resins, polyamide resins, bismaleimide resins, maleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, polyester resins, silicone resins, and acrylic resins. [7] The electromagnetic wave shielding film according to [2], wherein the impregnating resin is a thermoplastic resin, and the thermoplastic resin includes at least one selected from the group consisting of polyethylene, polypropylene, fluororesin, polyethylene terephthalate, polyethylene naphthalate, and polyimide. [8] The electromagnetic wave shielding film according to [2], wherein the impregnating resin is a thermosetting resin, and the thermosetting resin includes at least one selected from the group consisting of epoxy resins, allylated epoxy resins, allylated polyphenylene ether resins, phenolic resins, polyimide resins, polyamide resins, bismaleimide resins, maleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, polyester resins, silicone resins, and acrylic resins.

[0011] The electromagnetic wave shielding film of the present invention uses a carbon nanotube nonwoven fabric, and by using a laminated film in which a resin film is laminated on the front and back sides of the carbon nanotube nonwoven fabric, or an impregnated film impregnated with a thermosetting resin, the characteristics of the carbon nanotube as an electromagnetic wave shielding material can be fully utilized. Furthermore, by using a configuration in which a release film is attached to the laminated film or the impregnated film via an adhesive layer, handling is also easy. In other words, an electromagnetic wave shielding film that is excellent in electromagnetic wave shielding properties and electromagnetic wave shielding workability is provided. Effect of the Invention

[0012] The electromagnetic wave shielding film of the present invention can fully exhibit the properties as an electromagnetic wave shielding material using carbon nanotubes, and is easy to handle. [Brief description of the drawings]

[0013] [Figure 1A] 1 is a longitudinal sectional view that illustrates a schematic example of a first electromagnetic wave shielding film having a five-layer structure. [Figure 1B] FIG. 2 is a longitudinal sectional view that illustrates a schematic example of a second electromagnetic wave shielding film having a three-layer structure. [Diagram 2] FIG. 1 is a perspective view that typically shows an example of an electromagnetic wave shielding film having a five-layer structure wound into a roll like glass cloth. [Diagram 3] FIG. 2 is a perspective view showing a schematic example of a state in which a roll-shaped electromagnetic wave shielding film is cut into a tape shape. [Figure 4A] 1 is a longitudinal cross-sectional view that illustrates a schematic example of an example in which a release film is peeled off from a first electromagnetic shielding film having a five-layer structure and the film is attached to the surface of an electronic component. FIG. [Figure 4B] 10 is a longitudinal cross-sectional view that illustrates a schematic example of an example in which a release film is peeled off from a second electromagnetic shielding film having a three-layer structure and the film is attached to the surface of an electronic component. FIG. [Diagram 5] FIG. 1 is a perspective view showing a schematic example of a copper wiring surface wrapped with an electromagnetic wave shielding film cut into a tape shape. [Figure 6]FIG. 1 is a longitudinal sectional view showing a schematic example of an example in which a circuit board is entirely covered with an electromagnetic wave shielding film. [Figure 7] FIG. 2 is a schematic diagram of a measurement system for electromagnetic wave shielding characteristics in the examples. [Figure 8] FIG. 1 is a schematic diagram of a measurement system for electromagnetic wave shielding characteristics in the low frequency range. [Figure 9A] 1 is a chart showing the results of measuring the electromagnetic wave shielding properties of copper foil in the 100 to 6000 MHz range. [Figure 9B] 1 is a chart showing the results of measuring the electromagnetic wave shielding properties of the adhesive electromagnetic wave shielding film used in Example 7 in the 100 to 6000 MHz range. [Figure 10] 13 is a chart showing the results of measuring the transmission attenuation at 60 to 90 GHz in the adhesive electromagnetic wave shielding film used in Example 7. [Figure 11] 1 is a photograph showing the appearance, including the surface of the pressure-sensitive adhesive layer, of a prototype example of an electromagnetic wave shielding film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. The electromagnetic wave shielding film of the present invention uses a carbon nanotube nonwoven fabric having a resistivity of 0.005 Ω·cm or less, a thickness of 500 μm or less, and a longitudinal / lateral tensile strength ratio of 0.5 to 2.0, with the longitudinal direction being the direction in which the tensile strength is greatest and the transverse direction being the direction perpendicular to the longitudinal direction, and comprises (A) a laminated film having a total thickness of 10 to 1000 μm obtained by laminating a resin film on both sides of the carbon nanotube nonwoven fabric, or (B) an impregnated film having a total thickness of 10 to 1000 μm obtained by impregnating the carbon nanotube nonwoven fabric with a resin. The electromagnetic wave shielding film comprises a pressure-sensitive adhesive layer laminated on one side of the laminated film or impregnated film, and a release film laminated on the adhesive surface of the pressure-sensitive adhesive layer. Hereinafter, the electromagnetic wave shielding film having (A) the laminate film will also be referred to as a first electromagnetic wave shielding film, and the electromagnetic wave shielding film having (B) the impregnated film will also be referred to as a second electromagnetic wave shielding film.

[0015] <Carbon nanotube nonwoven fabric> The carbon nanotube nonwoven fabric used in the present invention has a thickness of 500 μm or less, preferably 5 to 300 μm. The carbon nanotube nonwoven fabric is made of a plurality of carbon nanotubes intertwined with each other. The carbon nanotubes constituting the carbon nanotube nonwoven fabric are single-walled carbon nanotubes, multi-walled carbon nanotubes, or a mixture thereof, and although the diameter and length of these are not particularly limited, they generally have a diameter of 50 nm or less and a length of 2 mm or less. The carbon nanotube nonwoven fabric used in the present invention is preferably made of carbon nanotubes having a length of 10 to 500 μm intertwined with each other. Carbon nanotubes can be produced by reacting a carbon source such as methane with a catalyst such as ferrocene in the gas phase at temperatures of 1000°C to 1500°C. In order to enhance the electrical conductivity of such nonwoven fabric, a highly conductive nonwoven fabric having a resistivity of 0.005 Ω·cm or less, preferably 0.003 Ω·cm or less, is used. Carbon nanotube nonwoven fabrics can be produced by directly stretching carbon nanotubes, pressing them, etc. Carbon nanotubes can also be suspended in water or an organic solvent, filtered or made into a sheet using a papermaking method, and then dried to produce a nonwoven fabric.

[0016] Depending on the manufacturing method, the carbon nanotube nonwoven fabric may have anisotropy in the density of the nonwoven fabric. As a result, the electric field attenuation rate may become anisotropic, and the electric field attenuation rate may decrease. Therefore, a carbon nanotube nonwoven fabric without anisotropy is selected and used. Whether the nonwoven fabric is uniformly entangled in the longitudinal and transverse directions can be easily determined by measuring the tensile strength in various directions of the nonwoven fabric, and determining the longitudinal / transverse tensile strength ratio when the direction in which the tensile strength is maximum is the longitudinal direction and the direction perpendicular to the longitudinal direction is the transverse direction. The carbon nanotube nonwoven fabric has a longitudinal / transverse tensile strength ratio of 0.5 to 2.0, preferably 0.6 to 1.85. Within this range, an appropriate electromagnetic wave shielding effect can be obtained in the high frequency vibration direction.

[0017] Commercially available carbon nanotube nonwoven fabrics having the above-mentioned properties include nonwoven fabrics with a thickness of 20 to 80 μm, such as MIRALON (manufactured by Huntsman, thickness 20 μm, resistivity 3.5E-03 (Ω·cm), tensile strength ratio 1.30).

[0018] In addition, single-walled or multi-walled carbon nanotube powder can be dispersed in a solvent, such as water or an organic solvent such as alcohol or N-methyl-2-pyrrolidone (NMP), and coated on a support film using a coater and dried to produce a nonwoven fabric. Nonwoven fabric can also be produced by filtering using filter paper and drying the CNTs on the filter paper. The amount of carbon nanotubes added per 100 parts by mass of the solvent is preferably 0.01 to 5 parts by mass, more preferably 0.01 to 2 parts by mass, and even more preferably 0.05 to 0.5 parts by mass. If the amount added is within this range, the viscosity of the dispersion liquid is appropriate in the above-mentioned production method, and it is also advantageous in terms of cost. Furthermore, an ionic surfactant can be used to improve the dispersibility and conductivity of carbon nanotubes. Examples of ionic surfactants include sodium deoxycholate, sodium cholate, sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate, sodium dodecyldiphenyloxidesulfonate, and cetyltrimethylammonium bromide. These may be used alone or in combination of two or more. Among them, sodium deoxycholate is particularly preferred. The amount of the ionic surfactant added per part by mass of carbon nanotubes is preferably 0.05 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, and even more preferably 1 to 10 parts by mass. If the amount added is within this range, the dispersion of carbon nanotubes is sufficient, the adhesion and bonding with thermoplastic resins and thermosetting resins is sufficient, and there is no bleeding onto the film surface. The nonwoven fabric made from the dispersion containing the ionic surfactant may be immersed in water or an organic solvent to remove the ionic surfactant. The organic solvent is preferably an alcohol such as methanol, ethanol, or IPA, or NMP.

[0019] In the electromagnetic wave shielding film of the present invention, a carbon nanotube nonwoven fabric having a silica layer on the surface of the carbon nanotube fibers may be used. For example, the carbon nanotube nonwoven fabric may be treated with a polysilazane compound or the like to form a silica layer on the fiber surface of the carbon nanotube nonwoven fabric.

[0020] In the electromagnetic wave shielding film of the present invention, in order to improve the wettability with thermosetting resins such as epoxy resins, polyimide resins, and bismaleimide resins, it is also possible to surface treat the fiber surface of the carbon nanotube nonwoven fabric with a sizing agent, i.e., a diluted solution of a thermosetting resin. Furthermore, by treating the surface of the carbon nanotube nonwoven fabric with a coupling agent, the carbon nanotube nonwoven fabric and the resin are adhered closely to each other, thereby improving the durability of the electromagnetic wave shielding sheet. Examples of the coupling agent include silane coupling agents and alkoxide compounds such as titanium and aluminum. Among them, silane coupling agents are preferred, and examples of preferred silane coupling agents include compounds represented by the general formula Y-Si-X3. Here, Y is an organic group having a functional group such as an amino group, an epoxy group, a hydroxyl group, a carboxyl group, a vinyl group, a methacryl group, or a mercapto group, and X is a hydrolyzable functional group such as an alkoxy group. Specific examples of the compound represented by the general formula Y-Si-X3 include γ-glycidoxypropyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-aminobenzyltriethoxysilane, and γ-aminophenyltriethoxysilane. Also usable are silane compounds such as polysilazane.

[0021] In the electromagnetic wave shielding film of the present invention, an inorganic material may be added to the carbon nanotube nonwoven fabric. Examples of the inorganic material include conductive inorganic materials and insulating inorganic materials. By filling the gaps between the entangled fibers of the carbon nanotube nonwoven fabric with a conductive inorganic material, such as inorganic particles, inorganic fibers, or metal particles, it is possible to further increase the electrical conductivity and improve the electromagnetic wave shielding performance in the frequency band from millimeter waves to terahertz. Among the conductive inorganic materials, examples of the inorganic particles include carbon black, carbon nanotubes, graphene, graphite, etc., examples of the inorganic fibers include short carbon fibers, etc., and examples of the metal particles include particles made of metals such as copper, iron, silver, and gold. In addition, resin particles surface-coated with these metals may be used as the conductive inorganic material. By using inorganic particles or inorganic fibers as insulating inorganic materials with high thermal conductivity, the thermal conductivity of the carbon nanotube nonwoven fabric can be further increased, and the thermal conductivity of the carbon nanotube nonwoven fabric can be set to, for example, 50 to 80 W / mK. Among the insulating inorganic materials, examples of inorganic particles include silica, zinc oxide, alumina, boron nitride, and aluminum nitride. Examples of inorganic fibers include alumina short fibers, quartz fibers, and glass fibers.

[0022] The shape of the inorganic material is not particularly limited, but an average particle size of 0.5 μm to 30 μm is preferred from the standpoint of heat dissipation and electrical conductivity. The average particle size of the inorganic material is the D50 value measured by a laser diffraction method.

[0023] The inorganic material can be directly sprayed onto the carbon nanotube nonwoven fabric and fixed thereon. The inorganic material can be sprayed onto the carbon nanotube nonwoven fabric by any method, such as packing the inorganic material into the carbon nanotube nonwoven fabric with a press or laminator, dispersing the inorganic material in any solvent, spraying the dispersion onto the carbon nanotube nonwoven fabric with a spray, and then drying and removing the solvent, or a combination of these methods. Any solvent can be used as the solvent for the dispersion liquid, but a highly volatile solvent is preferable, for example, water, alcohol such as ethanol and isopropyl alcohol, acetone, toluene, hydrocarbon-based solvents, silicone-based solvents, etc. The concentration of the dispersion liquid is preferably 0.1 to 100 parts by mass with respect to 100 parts by mass of the inorganic material. When the inorganic material is fixed by scattering it on the carbon nanotube nonwoven fabric, the amount of the material to be fixed is preferably 0.01 to 100 parts by mass per 100 parts by mass of the carbon nanotube nonwoven fabric.

[0024] Additionally, a metal foil such as copper or aluminum can be laminated onto the nonwoven fabric of carbon nanotubes.

[0025] <Resin film of the first electromagnetic wave shielding film> In the first electromagnetic wave shielding film, the resin film in the laminate film is a thermoplastic resin film or a thermosetting resin film. (Thermoplastic resin film) Of these, the thermoplastic resin film preferably has a softening point of 400° C. or lower in terms of film molding and electromagnetic wave shielding film processing. The lower limit of the softening point is not particularly limited, but is, for example, 70° C. or higher. The softening point of the thermoplastic resin can be measured according to JIS K7196-1991 "Softening temperature test method by thermomechanical analysis of thermoplastic plastic films and sheets". Examples of the thermoplastic resin in the film include polyethylene, polypropylene, fluororesin, polyethylene terephthalate, polyethylene naphthalate, polyimide, polyphenylene ether, polyether ether ketone, polyether ketone, polyether sulfone, etc. These may be used alone or in combination of two or more. Among them, polyethylene, polypropylene, polyethylene terephthalate, and polyethylene naphthalate are preferred from the viewpoint of processability as an electromagnetic wave shielding film. In addition, when heat resistance is required, polyimide films are preferred, and when chemical resistance and solvent resistance are further required, fluororesin films are preferred. Other components such as known additives may be added to the thermoplastic resin within the range that does not impair the effects of the present invention. The thermoplastic resin film to be used is a film obtained by previously processing a thermoplastic resin into a film having a thickness of preferably 5 to 200 μm, more preferably 10 to 100 μm.

[0026] (Thermosetting resin film) In the first electromagnetic wave shielding film, examples of the thermosetting resin in the laminate film include epoxy resin, allylated epoxy resin, allylated polyphenylene ether resin, phenol resin, polyimide resin, polyamide resin, bismaleimide resin, maleimide resin, cyanate resin, cyclopentadiene-styrene copolymer resin, polyester resin, silicone resin, acrylic resin, etc. These may be used alone or in combination of two or more. Among these, silicone resins and bismaleimide resins are preferred from the standpoint of heat resistance and flexibility.

[0027] The silicone resin used in the thermosetting resin film is not particularly limited as long as it is a thermosetting silicone resin composition, but it is preferable to use one or more resins selected from an addition curing type silicone resin composition containing an alkenyl group-containing organopolysiloxane, an organohydrogenpolysiloxane, and a hydrosilylation catalyst, and a condensation curing type silicone resin composition containing an alkoxysilyl group- and / or hydroxysilyl group-containing organopolysiloxane, a condensation catalyst, etc. From the viewpoint of various physical properties such as workability, storage stability, transparency, and electrical properties, an addition curing type silicone resin composition is particularly preferable. As the addition curing type silicone resin composition, an addition curing type silicone resin composition containing the following (A) alkenyl group-containing organopolysiloxane, (B) organohydrogenpolysiloxane having a resin structure, and (C) a platinum group metal catalyst is preferable.

[0028] (A) The alkenyl group-containing organopolysiloxane is an organopolysiloxane having a resin structure. The organopolysiloxane having a resin structure (i.e., a three-dimensional network structure) is an organopolysiloxane having an alkenyl group-containing organopolysiloxane having a resin structure (i.e., a three-dimensional network structure), R 1 SiO 1.5 Units, R 2 2SiO units, and R 3 a R 4 b SiO (4-a-b) / 2 It has units (where R 1 , R 2 , and R 3represents a methyl group, an ethyl group, a propyl group, a cyclohexyl group, or a phenyl group; R 4 represents a vinyl group or an allyl group, a is 0, 1 or 2, b is 1 or 2, and a+b is 2 or 3; 2 The organopolysiloxane has a resin structure partially containing a structure in which at least a portion of 2SiO units are continuously repeated, the number of repetitions being 5 to 300, preferably 10 to 300, more preferably 15 to 200, and even more preferably 20 to 100.

[0029] In addition, the above R 2 The structure in which at least a portion of 2SiO units are continuously repeated and the number of repetitions is 5 to 300 means a linear diorganopolysiloxane chain structure represented by the following general formula. [ka] (Here, m is an integer from 5 to 300.)

[0030] R present in the organopolysiloxane of component (A) 2 At least a portion of the entire 2SiO units, preferably 50 mol % or more (50 to 100 mol %), particularly 80 mol % or more (80 to 100 mol %), preferably form a chain structure represented by the above general formula in the molecule.

[0031] In the molecule of the component (A), R 2 The 2SiO units act to extend the polymer molecules in a linear fashion, R 1 SiO 1.5 The units allow the polymer molecule to branch or form a three-dimensional network. 3 a R 4 b SiO (4-a-b) / 2 R in units 4 (vinyl group or allyl group) is R 3 c H d SiO (4-c-d) / 2It plays a role in curing the addition-curable silicone resin composition by undergoing a hydrosilylation addition reaction with hydrogen atoms bonded to silicon atoms of the units (i.e., SiH groups).

[0032] The molar ratio of the three essential siloxane units constituting the component (A), i.e., R 1 SiO 1.5 Unit:R 2 2SiO unit: R 3 a R 4 b SiO (4-a-b) / 2 The molar ratio of the units is preferably 90-24:75-9:50-1, particularly preferably 70-28:70-20:10-2 (but the total is 100) in view of the properties of the resulting cured product.

[0033] R 3 a R 4 b SiO (4-a-b) / 2 The unit is R. 3 R 4 SiO units, R 3 2R 4 SiO 0.5 Units, R 4 2SiO units, and R 3 R 4 2SiO 0.5 R indicates that the siloxane unit is one type selected from the group consisting of siloxane units or a combination of two or more types of siloxane units. 3 a R 4 b SiO (4-a-b) / 2 Regarding the units, the vinyl group and allyl group are preferably present in the organopolysiloxane in a total amount of 0.001 mol / 100 g or more, more preferably 0.025 mol / 100 g or more, and even more preferably 0.03 to 0.3 mol / 100 g.

[0034] Furthermore, when the weight average molecular weight of the component (A) in terms of polystyrene standards as determined by gel permeation chromatography (GPC) is in the range of 3,000 to 1,000,000, particularly 10,000 to 100,000, the polymer is solid or semi-solid, which is preferable in terms of workability, curability, etc.

[0035] Organopolysiloxanes having such a resin structure can be synthesized by combining the raw material compounds for each unit so that the three types of siloxane units described above are present in the resulting polymer in the desired molar ratio, and then carrying out cohydrolytic condensation, for example, in the presence of an acid.

[0036] In the organopolysiloxane of the component (A), 90 mol % or more (90 to 100 mol %), particularly 95 mol % or more (95 to 100 mol %) of the siloxane units constituting the component (A) are R 1 SiO 1.5 Units, R 2 2SiO units, and R 3 a R 4 b SiO (4-a-b) / 2 Of the three types of siloxane units, 0 to 10 mol %, particularly 0 to 5 mol % may be other siloxane units. Specifically, when the organopolysiloxane of component (A) is produced by cohydrolysis and condensation of the above-mentioned raw material compounds, R 1 SiO 1.5 Units, R 2 2SiO units and / or R 3 a R 4 b SiO (4-a-b) / 2 In addition to the units, siloxane units having silanol groups may be by-produced. The organopolysiloxane of component (A) may contain such silanol group-containing siloxane units in an amount of usually 10 mol % or less (0 to 10 mol %), preferably 5 mol % or less (0 to 5 mol %), based on the total siloxane units. Examples of the silanol group-containing siloxane units include those represented by the formula: 1 (HO)SiO units, R 1 (HO)2SiO 0.5 Units, R2 2(HO)SiO 0.5 Units, R 3 a R 4 b (HO)SiO (3-a-b) / 2 Units, R 3 a R 4 b (HO)2SiO (2-a-b) / 2 Units (where R 1 ~R 4 , a and b are as defined above.

[0037] The component (B) in the addition curable silicone resin composition is an organohydrogenpolysiloxane having a resin structure (i.e., a three-dimensional network structure), and R 1 SiO 1.5 Units, R 2 2SiO units, and R 3 c H d SiO (4-c-d) / 2 It has units (where R 1 , R 2 , R 3 is as above, c is 0, 1 or 2, d is 1 or 2, and c+d is 2 or 3; 2 The organohydrogenpolysiloxane has a resin structure partially containing a linear siloxane structure in which at least a portion of 2SiO units are continuously repeated, the number of repetitions being 5 to 300, preferably 10 to 300, more preferably 15 to 200, and even more preferably 20 to 100.

[0038] In addition, R 2 The structure in which at least a part of the 2SiO units are continuously repeated and the number of repetitions is 5 to 300 is, as described above with respect to the component (A), R 2 This means that at least a portion of the 2SiO units, preferably at least 50 mol % (50 to 100 mol %), and particularly at least 80 mol % (80 to 100 mol %), form the linear diorganopolysiloxane chain structure represented by the general formula (1) in the molecules of component (B).

[0039] In the molecule of component (B), R 2 The 2SiO units act to extend the polymer molecules in a linear fashion, R 1 SiO 1.5 The units allow the polymer molecule to branch or form a three-dimensional network. 3 c H d SiO (4-c-d) / 2 The hydrogen atoms bonded to silicon in the units undergo a hydrosilylation addition reaction with the alkenyl groups in component (A) above, thereby curing the addition-curable silicone resin composition.

[0040] The molar ratio of the three essential siloxane units constituting component (B), i.e., R 1 SiO 1.5 Unit:R 2 2SiO unit: R 3 c H d SiO (4-c-d) / 2 The molar ratio of the units is preferably 90-24:75-9:50-1, particularly preferably 70-28:70-20:10-2 (but the total is 100) in view of the properties of the resulting cured product.

[0041] The weight average molecular weight of the component (B) as calculated based on polystyrene standards by GPC is preferably in the range of 3,000 to 1,000,000, and more preferably 10,000 to 100,000, from the standpoint of workability and properties of the cured product.

[0042] Organohydrogenpolysiloxanes having such a resin structure can be synthesized by combining the raw materials for each unit so that the three types of siloxane units are present in the resulting polymer in the desired molar ratio, and then cohydrolyzing them.

[0043] In the organohydrogenpolysiloxane of component (B), 90 mol % or more (90 to 100 mol %), particularly 95 mol % or more (95 to 100 mol %) of the siloxane units constituting component (B) are R 1 SiO 1.5 Units, R 2 2SiO units, and R 3c H d SiO (4-c-d) / 2 Of the three types of siloxane units, 0 to 10 mol %, particularly 0 to 5 mol % may be other siloxane units. Specifically, when the organopolysiloxane of component (B) is produced by cohydrolysis and condensation of the above-mentioned raw material compounds, R 1 SiO 1.5 Units, R 2 2SiO units, and R 3 c H d SiO (4-c-d) / 2 In addition to the units, siloxane units having silanol groups may be by-produced. The organopolysiloxane of component (B) may contain such silanol group-containing siloxane units in an amount of usually 10 mol % or less (0 to 10 mol %), preferably 5 mol % or less (0 to 5 mol %) based on the total siloxane units. Examples of the silanol group-containing siloxane units include those represented by the formula: 1 (HO)SiO units, R 1 (HO)2SiO 0.5 Units, R 2 2(HO)SiO 0.5 Units, R 3 c H d (HO)SiO (3-c-d) / 2 Units, R 3 c H d (HO)2SiO (2-c-d) / 2 Units (where R 1 ~R 3 , c and d are as defined above.

[0044] The amount of organohydrogenpolysiloxane in component (B) is preferably an amount such that the molar ratio of hydrogen atoms bonded to silicon atoms (SiH groups) in component (B) to the total amount of vinyl groups and allyl groups in component (A) is 0.1 to 4.0, particularly preferably 0.5 to 3.0, and even more preferably 0.8 to 2.0. If it is 0.1 or more, the curing reaction proceeds and a silicone cured product can be obtained, while if it is 4.0 or less, there will not be a large amount of unreacted SiH groups remaining in the cured product, and there is no risk of the physical properties of the cured product changing over time.

[0045] The platinum group metal catalyst (C) in the addition curing silicone resin composition is blended to promote the addition curing reaction, and includes platinum, palladium, and rhodium catalysts. From the viewpoint of cost, platinum, platinum black, platinum-based catalysts such as chloroplatinic acid, for example, HPtCl6·mH2O, K2PtCl6, KHPtCl6·mH2O, K2PtCl4, K2PtCl4·mH2O, PtO2·mH2O, (m is a positive integer), and complexes of these catalysts with hydrocarbons such as olefins, alcohols, or vinyl group-containing organopolysiloxanes can be exemplified. These catalysts can be used alone or in combination of two or more.

[0046] The amount of component (C) used may be an amount effective for curing, and is usually within the range of 0.1 to 500 ppm, particularly preferably 0.5 to 100 ppm, calculated as platinum group metal by mass relative to the total amount of components (A) and (B).

[0047] In addition to the above-mentioned components (A), (B), and (C), the addition-curable silicone resin composition may contain various known additives, such as inorganic fillers and adhesive aids, if necessary. Inorganic fillers may be added for the purpose of reducing the thermal expansion coefficient, etc. Examples of inorganic fillers include reinforcing inorganic fillers such as fumed silica, fumed titanium dioxide, and fumed alumina, and non-reinforcing inorganic fillers such as fused silica, alumina, calcium carbonate, calcium silicate, titanium dioxide, ferric oxide, and zinc oxide. These inorganic fillers can be appropriately blended in a total amount of 100 parts by mass or less (0 to 100 parts by mass) per 100 parts by mass of the total amount of the components (A) and (B). In order to impart adhesion to the addition curing silicone resin composition, an adhesion promoter can be added as necessary. Examples of the adhesion promoter include linear or cyclic organosiloxane oligomers having 4 to 50 silicon atoms, preferably about 4 to 20 silicon atoms, each molecule containing at least two, preferably two or three functional groups selected from hydrogen atoms (SiH groups) bonded to silicon atoms, alkenyl groups (e.g., Si-CH=CH2 groups) bonded to silicon atoms, alkoxysilyl groups (e.g., trimethoxysilyl groups), and epoxy groups (e.g., glycidoxypropyl groups and 3,4-epoxycyclohexylethyl groups), and organooxysilyl-modified isocyanurate compounds represented by the following general formula (2) and / or their hydrolysis condensates (organosiloxane-modified isocyanurate compounds).

[0048] As specific examples of the bismaleimide resin used in the thermosetting resin film, reference is made to the examples described later in the section (Thermosetting Resin). Other components such as known additives may be added to the thermosetting resin within the range that does not impair the effects of the present invention. The thermosetting resin film to be used is a film in which the thermosetting resin is preliminarily processed to a thickness of preferably 5 to 200 μm, more preferably 10 to 100 μm.

[0049] <Resin of the second electromagnetic shielding film> In the second electromagnetic wave shielding film, the impregnated resin in the impregnated film is a thermoplastic resin or a thermosetting resin. (thermoplastic resin) In the second electromagnetic shielding film, the thermoplastic resin can be used in a liquid state when it is impregnated into the carbon nanotube nonwoven fabric, by dissolving it in a solvent, or, in the case of a fluororesin, by dispersing it in a dispersion solvent such as water to form a slurry-like resin. After the carbon nanotube nonwoven fabric is impregnated with the thermoplastic resin thus liquidized, the solvent or dispersion solvent is heated and dried to remove the solvent, thereby forming an impregnated film. In the second electromagnetic wave shielding film, examples of the thermoplastic resin in the impregnated film include polyethylene, polypropylene, fluororesin, polyethylene terephthalate, polyethylene naphthalate, polyimide, polyphenylene ether, polyether ether ketone, polyether ketone, polyether sulfone, etc. These may be used alone or in combination of two or more. Other components such as known additives may be added to the thermoplastic resin within the range that does not impair the effects of the present invention.

[0050] (thermosetting resin) In the second electromagnetic wave shielding film, examples of the thermosetting resin in the impregnated film include epoxy resin, allylated epoxy resin, allylated polyphenylene ether resin, phenol resin, polyimide resin, polyamide resin, bismaleimide resin, maleimide resin, cyanate resin, cyclopentadiene-styrene copolymer resin, polyester resin, silicone resin, acrylic resin, etc. These may be used alone or in combination of two or more. Among these, the following epoxy resins and bismaleimide resins are preferred.

[0051] A preferred example of the epoxy resin is an epoxy resin having two or more glycidyl groups in one molecule. Examples of the epoxy resin used in the present invention include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, and bisphenol S type epoxy resin; novolac type epoxy resins such as epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, phenol novolac type epoxy resin, and cresol novolac type epoxy resin; and polyfunctional epoxy resins. These epoxy resins may be used alone or in combination of two or more.

[0052] As the curing agent for the epoxy resin, any curing agent that has a phenolic hydroxyl group or an amino group having active hydrogen and forms a crosslinked structure with the epoxy resin can be used. As the curing agent having a phenolic hydroxyl group, any structure of phenolic resin having a phenolic hydroxyl group can be used. As the curing agent having an amino group, an aromatic amine curing agent that can obtain a cured epoxy resin having high heat resistance and high elasticity is preferable.

[0053] As the bismaleimide resin, a bismaleimide resin represented by the following general formula (1) or formula (2) is preferably used because of its excellent heat resistance, low elasticity, toughness, and adhesiveness. [ka] (In formula (1), A represents a hydrocarbon group derived from a dimer acid skeleton.) [ka] (In formula (2), B is independently a tetravalent organic group having a cyclic structure, X is independently a divalent hydrocarbon group having 6 to 200 carbon atoms, at least one of which is a hydrocarbon group derived from a dimer acid skeleton, and n is 1 to 100.)

[0054] Dimer acid is a liquid dibasic acid mainly composed of a dicarboxylic acid having 36 carbon atoms, which is produced by dimerization of unsaturated fatty acids having 18 carbon atoms, derived from natural products such as vegetable oils and fats. Dimer acids do not have a single skeleton, but have multiple structures, and there are several types of isomers. Representative dimer acids are classified as linear, monocyclic, aromatic, and polycyclic. In this specification, the dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxy group of a dimer acid is replaced with a primary aminomethyl group, and the average structure of the hydrocarbon group derived from the dimer acid skeleton is -C. 36 H 70 It may be written as -.

[0055] A representative bismaleimide resin of the formula (1) is a bismaleimide resin represented by the following formula (3) (SLK-6895; trade name, manufactured by Shin-Etsu Chemical Co., Ltd.). [ka] (C 36 H 72 is a hydrocarbon group derived from the dimer acid skeleton) In formula (2), B independently represents a tetravalent organic group having a cyclic structure, and among these, any of the tetravalent organic groups represented by the following structural formulas is preferable.

[0056] [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (2).)

[0057] In addition, in formula (2), X is independently a divalent hydrocarbon group having 6 to 200 carbon atoms, preferably 8 to 100, and more preferably 10 to 50. Among these, it is preferable that the divalent hydrocarbon group is a branched divalent hydrocarbon group in which one or more hydrogen atoms are substituted with an alkyl or alkenyl group having 6 to 200 carbon atoms, preferably 8 to 100, and more preferably 10 to 50 carbon atoms. The branched divalent hydrocarbon group may be either a saturated aliphatic hydrocarbon group or an unsaturated hydrocarbon group, and may have an alicyclic structure or an aromatic ring structure in the middle of the molecular chain. At least one of X in formula (2) is a hydrocarbon group derived from a dimer acid skeleton.

[0058] In the formula (2), n is 1 to 100, preferably 1 to 60, and more preferably 1 to 50. If n is too large, the solubility and flowability may decrease, and moldability such as impregnation may be poor.

[0059] A representative bismaleimide resin of the formula (2) is the following resin of the formula (4) (SLK-3000; trade name, manufactured by Shin-Etsu Chemical Co., Ltd.). [ka]

[0060] The bismaleimide resins of formula (1) and formula (2) may be used alone or in combination of two or more.

[0061] Representative bismaleimide resins include the above-mentioned SLK-6895 (manufactured by Shin-Etsu Chemical Co., Ltd.) and SLK-3000 (manufactured by Shin-Etsu Chemical Co., Ltd.), as well as the SLK-2000 series (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0062] The amount of the bismaleimide resin impregnated into the carbon nanotube nonwoven fabric is preferably 10 to 1000 parts by mass per 100 parts by mass of the nonwoven fabric.

[0063] When using a bismaleimide resin as the thermosetting resin, it is preferable to use a reaction initiator for the bismaleimide resin as a curing catalyst. The reaction initiator for the bismaleimide resin is not particularly limited as long as it accelerates the crosslinking reaction, and examples thereof include ion catalysts such as imidazoles, organic phosphorus compounds, tertiary amines, quaternary ammonium salts, boron trifluoride amine complexes, organophosphines, and organophosphonium salts; organic peroxides such as diallyl peroxide, dialkyl peroxide, peroxide carbonate, and hydroperoxide; and radical polymerization initiators such as azoisobutyronitrile. Among these, organic peroxides are preferred, and examples of the organic peroxides include dicumyl peroxide, t-butyl peroxybenzoate, t-amyl peroxybenzoate, dibenzoyl peroxide, diuraloyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,1-di(t-butylperoxy)cyclohexane, di-t-butyl peroxide, and dibenzoyl peroxide. The reaction initiator is preferably blended in an amount of 0.05 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the bismaleimide resin. The reaction initiator may be used alone or in combination of two or more kinds.

[0064] The bismaleimide resins represented by the general formulas (1) and (2) may be mixed with other thermosetting resins. By using the bismaleimide resin alone or in combination with other thermosetting resins as the thermosetting resin to be impregnated into the carbon nanotube nonwoven fabric, it is possible to impart greater toughness to the fabric. The bismaleimide resins represented by the general formulas (1) and (2) may be mixed with the above-mentioned thermoplastic resins for use.

[0065] In the second electromagnetic wave shielding film, other components such as known additives may be added to the thermosetting resin in the impregnated film within the range that does not impair the effects of the present invention.

[0066] <Components added to the resin in the first and second electromagnetic wave shielding films> The first and second electromagnetic wave shielding films may contain other components such as known additives within the scope of the present invention. Examples of other components include coupling agents and inorganic materials. The coupling agents and inorganic materials may be added to either the thermoplastic resin film and the thermosetting resin film of the first electromagnetic wave shielding film, or the thermoplastic resin and the thermosetting resin of the second electromagnetic wave shielding film. In particular, addition to the thermosetting resin composition, which is the raw material of the thermosetting resin film, is preferred.

[0067] Coupling agents can be used to improve the wetting and adhesive strength between the carbon nanotube nonwoven fabric and the resin. Specific examples of coupling agents include those mentioned above as additives to the carbon nanotube nonwoven fabric, and the descriptions thereof are incorporated herein by reference. When such a coupling agent is added, the amount used is suitably in the range of 0.5 to 20 parts by mass per 100 parts by mass of the thermoplastic resin or thermosetting resin. The addition to the thermoplastic resin can be carried out, for example, by preparing a thermoplastic resin dissolved in a solvent and adding the coupling agent thereto.

[0068] Examples of the inorganic material include conductive inorganic materials and insulating inorganic materials. The conductive inorganic material can further increase the electrical conductivity and can improve the electromagnetic wave shielding performance in the frequency band from millimeter waves to terahertz bands. The insulating inorganic material can further increase the thermal conductivity of the carbon nanotube nonwoven fabric. Specific examples of the conductive inorganic material and the insulating inorganic material include the examples mentioned above as additives to the carbon nanotube nonwoven fabric, and the description thereof is referred to. In the first electromagnetic shielding film, the inorganic material may be laminated as a thermoplastic resin film or a thermosetting resin film, and in the second electromagnetic shielding film, the inorganic material may be dispersed in a thermoplastic resin or a thermosetting resin, which is then impregnated into the carbon nanotube nonwoven fabric. When an inorganic material is added, the amount of the inorganic material added is preferably 5 to 60 parts by mass, and more preferably 10 to 50 parts by mass, per 100 parts by mass of the thermoplastic resin or the thermosetting resin.

[0069] <Laminated film of the first electromagnetic wave shielding film> In the first electromagnetic wave shielding film, the laminated film is formed by laminating resin films on the front and back surfaces of a carbon nanotube nonwoven fabric. The total thickness of the laminated film is 10 to 1000 μm, preferably 20 to 500 μm. If the total thickness of the laminated film is within this range, the characteristics of the carbon nanotube as an electromagnetic wave shielding material can be fully utilized. Furthermore, by attaching a release film to the laminated film via an adhesive layer, handling is also easy. The total thickness of the laminate film is the thickness when the laminate film is completed; if a thermoplastic resin film is heated and pressurized to be laminated onto a carbon nanotube nonwoven fabric, it is the total thickness after that; if the resin film is a thermosetting resin film that hardens after lamination, it is the total thickness after hardening.

[0070] <Impregnated film of the second electromagnetic wave shielding film> In the second electromagnetic wave shielding film, the impregnated film is obtained by impregnating a carbon nanotube nonwoven fabric with an impregnating resin, that is, a thermoplastic resin or a thermosetting resin. The total thickness of the impregnated film is 10 to 1000 μm, preferably 20 to 500 μm. If the total thickness of the impregnated film is within this range, the characteristics of the carbon nanotube as an electromagnetic wave shielding material can be fully utilized. Furthermore, by attaching a release film to the impregnated film via an adhesive layer, handling is also easy. The total thickness of the impregnated film is the thickness when the impregnated film is completed, that is, the total thickness of the impregnated film after impregnating the carbon nanotube nonwoven fabric with a thermoplastic resin solution and then heating and drying to remove the solvent, and also, in the case of hardening the thermosetting resin after impregnating the carbon nanotube nonwoven fabric, the total thickness after hardening.

[0071] <Adhesive layer> In the first and second electromagnetic wave shielding films, an adhesive is used to attach and fix the electromagnetic wave shielding film to the surface of an electronic component or a circuit board. Any available adhesive can be used, but acrylic resin or silicone resin is preferred, as products with a wide range of adhesive strengths are available. Representative examples of silicone resins include KR100, KR130, KR3701, and KR3704 manufactured by Shin-Etsu Chemical Co., Ltd. This type of adhesive is diluted with a solvent such as toluene and a catalyst is added, then it is applied to one side of an electromagnetic wave shielding film and heat-cured at a temperature of 100°C to 150°C for several minutes to remove the solvent, forming an adhesive layer. The thickness of the adhesive layer can be adjusted by changing the dilution degree of the solvent. The adhesive strength can also be easily adjusted by mixing a light adhesive with a heavy adhesive. If the adhesive is to be attached to a heatable member, a thermosetting adhesive or adhesive can be used. The thickness of the pressure-sensitive adhesive layer is preferably 10 to 100 μm, and more preferably 20 to 70 μm.

[0072] <Release film> In the first and second electromagnetic wave shielding films, the release film can be made of polypropylene, PET, polyethylene film, fluororesin film, etc. If the pressure-sensitive adhesive layer applied to the electromagnetic wave shielding film is difficult to peel off from the release film, a release film treated with a release agent can be used. The thickness of the release film is preferably 10 to 50 μm from the viewpoint of ease of use. A matte-finished film can also be used as the release film.

[0073] <Method of manufacturing electromagnetic wave shielding film> The first electromagnetic wave shielding film can be produced, for example, by a melt rolling method in which a resin film is laminated on the front and back surfaces of a carbon nanotube nonwoven fabric and heated to reduce the viscosity and laminate it on the carbon nanotube nonwoven fabric, or a transfer method in which a resin varnish is made into a film using a coater or the like and then transferred to the carbon nanotube nonwoven fabric using a press or laminator. As the resin film, a thermoplastic resin film or a thermosetting resin film can be used, and as the thermosetting resin film, an uncured, semi-cured, or completely cured thermosetting resin film can be used.

[0074] The melt rolling method is advantageous in various respects, such as not needing to remove the solvent and having a relatively good working environment. In the melt rolling method, the carbon nanotube nonwoven fabric is expanded to a required width using a bar or the like, and a film-formed thermoplastic resin or thermosetting resin is sandwiched between release paper from above and below, and then the release paper is peeled off and the fabric is fed to several pairs of heated metal rolls installed at approximately the same height in the direction of travel of the carbon nanotube nonwoven fabric, and the carbon nanotube nonwoven fabric is nipped to heat and press the thermoplastic resin or thermosetting resin to the carbon nanotube nonwoven fabric. In the melt rolling method, the nip pressure is a linear pressure, so it is better to increase the number of nip rolls in order to perform sufficient heating and pressing. Alternatively, the molding may be carried out by a molding press such as a heatable multi-stage press without using a heated metal roll.

[0075] In the transfer method, a base film is coated with a resin varnish, the solvent is dried to obtain a resin film, and then both sides of a carbon nanotube nonwoven fabric are sandwiched between the resin films and pressed together using a laminator or press to transfer the resin film to the carbon nanotube nonwoven fabric. Any film can be used as the base film, but resin films tend to peel off easily. PET film, PE film, PP film, Teflon (registered trademark) film, Aflex film, etc. are preferred. If necessary, the surface of the above-mentioned base film may be subjected to various surface treatments such as corona treatment, plasma treatment, or silicone treatment. Any solvent can be used for the resin varnish, but highly volatile solvents are preferred, such as alcohols such as ethanol and IPA, acetone, toluene, xylene, anisole, hydrocarbon solvents, and silicone solvents. The concentration of the resin varnish is preferably 0.1 to 200 parts by mass with respect to 100 parts by mass of the resin. As a method for coating the base film with the resin varnish, any method can be used, but it is preferable to use a spin coater or a bar coater because it is easy to use. The temperature for drying the resin film on the substrate film is preferably a temperature at which the thermosetting resin does not react, and is preferably 30°C to 120°C. In addition, when both sides of the carbon nanotube nonwoven fabric are sandwiched between resin films and pressed with a laminator or press to transfer the resin films to the carbon nanotube nonwoven fabric, pressure or heat can be applied as necessary.

[0076] After laminating the resin film on the carbon nanotube nonwoven fabric by the above-mentioned method, in the case of a thermosetting resin film, the semi-cured thermosetting resin film is cured by applying heat and pressure as necessary to produce an electromagnetic wave shielding film. By selecting the chemical structures of the thermoplastic and thermosetting resins in the resin film and the curing method of the thermosetting resin, it is possible to produce laminate films that are hard and tough, as well as flexible and conformable to different shapes.

[0077] The second electromagnetic wave shielding film can be produced, for example, by a wet method in which a thermoplastic resin or a thermosetting resin is dissolved in a solvent or dispersed in a dispersion solvent to reduce the viscosity, and then impregnated into a carbon nanotube nonwoven fabric. In the wet method, a carbon nanotube nonwoven fabric is impregnated with a thermoplastic resin or a thermosetting resin, and then the volatile solvent or dispersion solvent is removed to produce a resin film impregnated with the thermoplastic resin, or a prepreg impregnated with an uncured thermosetting resin. If the solvent remains in the prepreg, it may have a negative effect on molding and may cause problems such as a worsening of the working environment. For this reason, the amount of solvent remaining in the prepreg is 1% by mass or less, and preferably 0.5% by mass or less. The method of removing the solvent depends on the boiling point of the solvent used, but it can be easily achieved by heat treatment at 80°C to 150°C for about 10 minutes to 1 hour. By impregnating the carbon nanotube nonwoven fabric with a thermoplastic resin using the above-mentioned method, a thermoplastic resin-impregnated film is manufactured. In addition, after impregnating the carbon nanotube nonwoven fabric with a thermosetting resin using the above-mentioned method, the semi-cured thermosetting resin is cured by applying heat and pressure to manufacture a thermosetting resin-impregnated film.

[0078] Then, an adhesive layer is laminated on one side of the three-layer laminate film in the first electromagnetic wave shielding film or one side of the impregnated film in the second electromagnetic wave shielding film, and a release film is laminated on the adhesive surface of the adhesive layer to obtain the electromagnetic wave shielding film of the present invention.

[0079] By processing using such a molding method, it is possible to supply a large-area electromagnetic shielding film of a specified thickness in sheet or roll form, wound around a paper tube or the like.

[0080] The electromagnetic wave shielding film of the present invention processed in this manner is lightweight and has excellent electromagnetic wave shielding properties, processability, and ease of use, and is therefore suitable for components that require electromagnetic wave shielding properties, such as surface coatings for electronic circuit boards mounting a large number of electronic components, storage containers for automobile batteries and other devices that generate electromagnetic waves, motor components, and DC / DC converter sealing materials. Furthermore, it can also be used as a component or storage container for communication equipment that uses high frequencies of millimeter waves or higher and requires electromagnetic wave shielding and heat resistance.

[0081] 1A is a longitudinal sectional view showing a schematic example of a first electromagnetic wave shielding film. This electromagnetic wave shielding film 1a is a five-layered electromagnetic wave shielding film having a three-layer laminated film in which a resin film 3 is laminated on the front and back sides of a carbon nanotube nonwoven fabric 2, a pressure-sensitive adhesive layer 4 laminated on one side of the laminated film, and a release film 5 laminated on the adhesive surface of the pressure-sensitive adhesive layer 4.

[0082] This electromagnetic wave shielding film 1a can be processed by the molding method described above to produce a large-area electromagnetic wave shielding film with a predetermined thickness, and as shown in Figure 2, it can be wound into a roll like glass cloth to form the electromagnetic wave shielding film 6.Then, as shown in Figure 3, the rolled electromagnetic wave shielding film 6 can be cut into a tape shape and used as the electromagnetic wave shielding film 7 cut into a tape shape.

[0083] The first electromagnetic wave shielding film 1a having a five-layer structure can shield electromagnetic waves, for example, by peeling off the release film 5 and attaching it to the surface of an electronic component 8 provided on a printed wiring board 9, as shown in FIG. 4A. Similarly, the second electromagnetic wave shielding film 1b having a three-layer structure shown in FIG. 1B, i.e., an electromagnetic wave shielding film having an impregnated film 10 in which a carbon nanotube nonwoven fabric is impregnated with a resin, an adhesive layer 4 laminated on one side of the impregnated film 10, and a release film 5 laminated on the adhesive side of the adhesive layer 4, can shield electromagnetic waves, for example, by peeling off the release film 5 and attaching the impregnated film 10 to the surface of an electronic component 8 provided on a printed wiring board 9 as shown in FIG. 4B.

[0084] Furthermore, as shown in Fig. 5, electromagnetic waves can be shielded by wrapping the surface of copper wiring 11 with electromagnetic wave shielding film 7 cut into a tape shape. As shown in Fig. 6, the first electromagnetic wave shielding film 1a having a five-layer structure can shield electromagnetic waves by, for example, peeling off the release film 5 and attaching it to cover the entire circuit board 12 including the surfaces of electronic components 8 provided on a printed wiring board 9, as shown in Fig. 6. The same applies to the second electromagnetic wave shielding film 1b. EXAMPLES

[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The materials used in the examples and comparative examples are shown below. The physical properties and characteristic values ​​in the present invention were measured by the following methods.

[0086] material (1) Carbon nanotube nonwoven fabric Nonwoven fabric 1 MIRALON T01 (Huntsman) Thickness: 20μm, resistivity: 3.5E-03 (Ω·cm), tensile strength ratio: 1.30 Nonwoven fabric 2 A dispersion liquid was prepared by mixing 100 parts by mass of water and 0.05 parts by mass of single-walled carbon nanotubes (EC1.5-P manufactured by Meijo Nano Carbon Co., Ltd.) in a mixer (IFM-800D manufactured by Iwatani Corporation), and then filtered. The water was removed by drying at 80°C for 4 hours to obtain a single-walled carbon nanotube nonwoven fabric. This single-walled carbon nanotube nonwoven fabric had a thickness of 40 μm, a resistivity of 1.05E-03 (Ω cm), and a tensile strength ratio of 1.08. Nonwoven fabric 3 A dispersion liquid was prepared by mixing 100 parts by mass of water and 0.05 parts by mass of multi-walled carbon nanotubes (EC2.0-P, Meijo Nano Carbon Co., Ltd.) in a mixer (IFM-800D, Iwatani Corporation), and then the mixture was filtered and dried at 80°C for 4 hours to produce a nonwoven fabric. The nonwoven fabric was immersed in a 5% by mass polysilazane solution (X-45-870, Shin-Etsu Chemical Co., Ltd.) diluted with dibutyl ether for 30 seconds, then removed and cured at 150°C for 2 hours. The mass of the cured CNT nonwoven fabric increased by 44.3% by mass, and surface analysis showed that a silica layer was formed on the surface of the carbon nanotube fibers. The polysilazane-treated multi-walled carbon nanotube nonwoven fabric had a thickness of 42 μm, a resistivity of 1.60E-03 (Ω·cm), and a tensile strength ratio of 1.08. Nonwoven fabric 4 A dispersion was prepared by mixing 100 parts by mass of water, 0.4 parts by mass of single-walled carbon nanotubes (EC1.5-P, Meijo Nano Carbon Co., Ltd.), and 0.4 parts by mass of ionic surfactant sodium deoxycholate (Fujifilm Wako Pure Chemical Industries, Ltd.) in a mixer (IFM-800D, Iwatani Corporation). The dispersion was applied to a release-treated PET film (E7006, Toyobo Ester Co., Ltd.) with a doctor blade with a clearance of 1.5 mm, dried at 100°C for 1 hour, and peeled off from the PET film to obtain a nonwoven fabric. This ionic surfactant-containing single-walled carbon nanotube nonwoven fabric had a thickness of 20 μm, a resistivity of 7.50E-04 (Ω·cm), and a tensile strength ratio of 1.02. Nonwoven fabric 5 (comparative nonwoven fabric) A dispersion was prepared by mixing 100 parts by mass of water and 0.10 parts by mass of multi-walled carbon nanotubes (EC2.0-P manufactured by Meijo Nano Carbon Co., Ltd.) in a mixer (IFM-800D manufactured by Iwatani Corporation), and then filtered. The multi-walled carbon nanotube nonwoven fabric was obtained by drying at 80°C for 4 hours while pulling it in a uniaxial direction against the surface direction. This multi-walled carbon nanotube nonwoven fabric had a thickness of 182 μm, a resistivity of 5.50E-03 (Ω cm), and a tensile strength ratio of 2.32.

[0087] (2)Thermoplastic resin, thermosetting resin Thermoplastic resin film 1 Polypropylene film with a thickness of 30 μm (Silfan, manufactured by Gunze Co., Ltd.) Thermoplastic resin film 2 Thermoplastic fluororesin film with a thickness of 35 μm (Fluon PFA, manufactured by AGC) Thermosetting resin 1 Bismaleimide resin represented by the above formula (4) (SLK-3000, manufactured by Shin-Etsu Chemical Co., Ltd., number average molecular weight 5200) Thermosetting resin film 2 Silicone resin uncured film with a thickness of 40 μm (PLF-100D, Shin-Etsu Chemical Co., Ltd.) (3) Adhesive 1 KR100 (Shin-Etsu Chemical Co., Ltd.) (4) Release film 1 Release-treated PET film (thickness 40 μm) (manufactured by Shin-Etsu Film Co., Ltd.)

[0088] Measurement method (1) Tensile strength ratio The tensile strength of the nonwoven fabric was measured by cutting a 10mm x 100mm test piece from the fabric and measuring it with an autograph (AGS-500NS) manufactured by Shimadzu Corporation, and the average value of five measurements was taken as the tensile strength. The tensile strength was measured in various directions of the nonwoven fabric, and the direction in which the tensile strength was maximum was taken as the machine direction, and the direction perpendicular to the machine direction was taken as the machine direction, to obtain the machine direction / machine direction tensile strength ratio. (2) Specific resistance The surface resistivity of the carbon nanotube nonwoven fabric was measured using a Loresta-GX MCP-T700 (low resistance resistivity meter, manufactured by Nitto Seiko Analytech Co., Ltd.), a Hiresta-UX MCP-HT800 (high resistance resistivity meter, manufactured by Nitto Seiko Analytech Co., Ltd.), and an EC-80P (eddy current resistance meter, manufactured by NAPSON Co., Ltd.). The measured values ​​were used to calculate the resistivity. The resistivity was calculated using the following formula. Specific resistance (Ω cm) = surface resistivity (Ω / □) x thickness (cm) (3) Electromagnetic wave shielding properties As the electromagnetic shielding properties, the electromagnetic shielding film cut into a 12 cm square was used to measure the electric field attenuation in two perpendicular directions, the vertical and horizontal directions, at 70 GHz, using an electromagnetic shielding measuring device manufactured by Keycom. A schematic diagram of the measurement system is shown in Figure 7. The surface of the nonwoven fabric, which is a sample, was placed between two antennas on the y axis connected to a vector network analyzer (MS46522B, manufactured by Anritsu) so that the surface was perpendicular to the y axis, and the electromagnetic wave that transmitted through the sample was measured by irradiating it with an electromagnetic wave having an electric field vibration in the z axis direction, and the transmission attenuation (dB) was recorded. In addition, the angle of the sample was tilted 90 degrees around the y axis to measure the transmission attenuation (dB) in two directions, the vertical and horizontal directions, and the electric field attenuation was calculated. Moreover, the electromagnetic shielding characteristics in the low frequency range of 100 MHz to 6000 MHz were measured by the method shown in Fig. 8. An organic board (reference numeral 18 in Fig. 8 indicates a microstrip line that is generally used as a transmission line in wiring on a printed circuit board) on which various electronic components were mounted was wrapped with the measurement sample 13, and an AC magnetic field 19 was applied to the measurement sample 13 from a probe 17 placed above and spaced apart from the measurement sample 13, and the electromagnetic shielding characteristics in the range of 100 MHz to 6000 MHz were measured. Moreover, as an electromagnetic shielding characteristic in the high frequency range, the transmission attenuation (dB) from 60 GHz to 90 GHz was measured by the method shown in FIG.

[0089] Example 1 Thermoplastic resin film 1 was laminated on top and bottom of nonwoven fabric 1, and heat pressed at 150°C to produce a three-layer laminated film with a total thickness of 75 μm. One side of this three-layer film was coated with adhesive 1 to a thickness of 20 μm, and the film was heat-cured at 150°C for 1 hour, after which release film 1 was laminated to produce an electromagnetic wave shielding film consisting of five layers. As the shielding properties of the produced electromagnetic wave shielding film, the electric field attenuation rate was measured by the above-mentioned measurement method after peeling off the release film. The results are shown in Table 1. In addition, by peeling off the release film and covering it on an electronic circuit board on which a semiconductor element was mounted, a shielding film-covered circuit board that followed the unevenness of the circuit surface could be produced (Figure 4A). The shielding film could be easily peeled off from the shielding film-covered circuit board.

[0090] Example 2 A thermoplastic resin film 2 was laminated on the top and bottom of the nonwoven fabric 2, and heat-pressed at 325°C to produce a laminated film with a total thickness of 108 μm, which was laminated in three layers. One side of this three-layer film was treated with Ar plasma for 30 seconds, and adhesive 1 was applied to a thickness of 30 μm and heat-cured at 150°C for 1 hour, and then release film 1 was laminated to produce an electromagnetic wave shielding film consisting of five layers. As the shielding properties of the produced electromagnetic wave shielding film, the electric field attenuation rate was measured by the above-mentioned measurement method after peeling off the release film. The results are shown in Table 1. In addition, by peeling off the release film and covering it on an electronic circuit board on which a semiconductor element was mounted, a shielding film-covered circuit board that followed the unevenness of the circuit surface could be produced. The shielding film could be easily peeled off from the shielding film-covered circuit board.

[0091] Example 3 A toluene solution consisting of 100 parts by mass of thermosetting resin 1, 1 part by mass of curing catalyst (dicumyl peroxide (Percumyl D, manufactured by NOF Corp.)), and 200 parts by mass of toluene was prepared. Nonwoven fabric 1 was impregnated with this toluene solution, and then heated at 100°C for 10 minutes to dry and remove the toluene, thereby producing a nonwoven fabric impregnated with semi-cured bismaleimide resin. This nonwoven fabric was pressurized and cured at 180°C and 0.5 MPa for 1 hour to produce an impregnated film with a total thickness of 24 μm. One side of the resin-impregnated nonwoven fabric sheet was coated with adhesive 1 to a thickness of 30 μm and heat-cured, and then release film 1 was laminated to produce an electromagnetic wave shielding film consisting of three layers. In addition, the release film was peeled off and coated on an electronic circuit board on which a semiconductor element was mounted, thereby producing a shielding film-coated circuit board that followed the unevenness of the circuit surface. The shielding film could be easily peeled off from the shielding film-coated circuit board.

[0092] Example 4 A three-layer electromagnetic shielding film was produced in the same manner as in Example 3, except that the carbon nanotube nonwoven fabric was changed to nonwoven fabric 3. The total thickness of the impregnated film was 46 μm. The electric field attenuation rate was measured using this film. The results are shown in Table 1. In addition, by peeling off the release film and covering an electronic circuit board on which a semiconductor element was mounted, a shielding film-covered circuit board that conformed to the unevenness of the circuit surface could be produced. The shielding film could be easily peeled off from the shielding film-covered circuit board.

[0093] Example 5 A thermosetting resin film 2 was laminated on the top and bottom of the nonwoven fabric 1 to produce a laminated film with a total thickness of 94 μm, and then an electromagnetic wave shielding film consisting of five layers was produced in the same manner as in Example 2. However, the pressure molding temperature was 150° C. As the shielding properties of the produced electromagnetic wave shielding film, the release film was peeled off and then the electric field attenuation rate was measured by the above-mentioned measurement method. The results are shown in Table 1. In addition, by peeling off the release film and covering an electronic circuit board on which a semiconductor element was mounted, a shielding film-covered circuit board that followed the unevenness of the circuit surface could be produced. The shielding film could be easily peeled off from the shielding film-covered circuit board.

[0094] Example 6 An electromagnetic wave shielding film was produced in the same manner as in Example 5, except that the carbon nanotube nonwoven fabric was changed to nonwoven fabric 4. The total thickness of the laminated film was 98 μm. The electric field attenuation rate was measured using this film. The results are shown in Table 1. In addition, by peeling off the release film and covering an electronic circuit board on which a semiconductor element was mounted, a shielding film-covered circuit board that conformed to the unevenness of the circuit surface could be produced. The shielding film could be easily peeled off from the shielding film-covered circuit board.

[0095] Example 7 An organic substrate on which various electronic components were mounted was entirely wrapped with the electromagnetic shielding film having an adhesive layer on one side produced in Example 3, and the electromagnetic shielding properties in the 100 MHz to 6000 MHz range were compared with those of a 36 μm copper foil using the method shown in Figure 8. The results are shown in Figures 9(A) and (B).

[0096] Example 8 The 55 μm thick adhesive electromagnetic shielding film used in Example 7 was cut into a 50 mm square sheet, and the transmission attenuation in the high frequency range of 60 GHz to 90 GHz was measured according to the method shown in Fig. 7. The results are shown in Fig. 10.

[0097] Example 9 An organic substrate on which various electronic components were mounted was entirely wrapped with the electromagnetic wave shielding film having an adhesive layer on one side thereof, as produced in Example 3, and the electromagnetic wave shielding properties were evaluated in the range of 100 Hz to 1 MHz. Although a large amount of electromagnetic noise of about 10 dB occurred in the measured frequency band, the electromagnetic waves could be shielded by using the film of this example.

[0098] Comparative Example 1 An electromagnetic wave shielding film was produced in the same manner as in Example 5, except that the carbon nanotube nonwoven fabric was changed to nonwoven fabric 5. The total thickness of the laminated film was 260 μm. The electric field attenuation rate was measured using this film. The results are shown in Table 1. In addition, by peeling off the release film and covering an electronic circuit board on which a semiconductor element was mounted, a shielding film-covered circuit board that conformed to the unevenness of the circuit surface could be produced. The shielding film could be easily peeled off from the shielding film-covered circuit board.

[0099] [Table 1]

[0100] The electromagnetic wave shielding films of Examples 1 to 6, which used carbon nanotube nonwoven fabrics with a small longitudinal / lateral tensile strength ratio, had a large electric field attenuation rate. Furthermore, the adhesive electromagnetic wave shielding film of the present invention was able to shield all electromagnetic waves from the low frequency region of 100 Hz to the high frequency region of 90 GHz. Figure 11 shows the appearance of a prototype of an adhesive electromagnetic wave shielding film. [Industrial Applicability]

[0101] According to the present invention, it is easy to provide electromagnetic shielding for electronic components and wiring mounted inside an electronic device, and the electronic device can be made compatible with high-speed communications such as 5G and 6G, and therefore has extremely high industrial value and applicability. [Explanation of symbols]

[0102] 1a The first electromagnetic wave shielding film with a five-layer structure 1b The second electromagnetic wave shielding film with a three-layer structure 2. Carbon nanotube nonwoven fabric 3. Resin film 4 Adhesive layer 5 Release film 6. Electromagnetic wave shielding film rolled up 7 Electromagnetic shielding film cut into tape 8. Electronic Components 9 Printed Wiring Boards 10 Resin-impregnated nonwoven fabric (impregnated film) 11 Copper wiring 12 Circuit Board 13 Measurement sample 14 Antenna 15 Incident wave 16 Transmitted wave 17 Probe 18 Microstrip Line 19 AC magnetic field

Claims

1. a laminated film having a total thickness of 10 to 1000 μm, the laminate being obtained by laminating a resin film on both sides of a carbon nanotube nonwoven fabric having a resistivity of 0.005 Ω cm or less, a thickness of 500 μm or less, and a longitudinal / lateral tensile strength ratio of 0.5 to 2.0, the longitudinal direction being the direction in which the tensile strength is greatest and the transverse direction being the direction perpendicular to the longitudinal direction; A pressure-sensitive adhesive layer laminated on one surface of the laminate film; and a release film laminated on the adhesive surface of the adhesive layer.

2. an impregnated film having a total thickness of 10 to 1000 μm, which is obtained by impregnating a carbon nanotube nonwoven fabric with a resin, the carbon nanotube nonwoven fabric having a resistivity of 0.005 Ω cm or less, a thickness of 500 μm or less, and a longitudinal / lateral tensile strength ratio of 0.5 to 2.0, the longitudinal direction being the direction in which the tensile strength is greatest and the transverse direction being the direction perpendicular to the longitudinal direction; a pressure-sensitive adhesive layer laminated on one surface of the impregnated film; and a release film laminated on the adhesive surface of the adhesive layer.

3. 3. The electromagnetic shielding film according to claim 1, wherein the carbon nanotubes in the carbon nanotube nonwoven fabric are single-walled carbon nanotubes, multi-walled carbon nanotubes, or a mixture thereof.

4. 2. The electromagnetic shielding film according to claim 1, wherein the resin film is a thermoplastic resin film, and the softening point of the thermoplastic resin in the film is 400° C. or lower.

5. 5. The electromagnetic shielding film according to claim 4, wherein the thermoplastic resin in the thermoplastic resin film contains at least one selected from the group consisting of polyethylene, polypropylene, fluororesin, polyethylene terephthalate, polyethylene naphthalate, and polyimide.

6. 2. The electromagnetic wave shielding film according to claim 1, wherein the resin film is a thermosetting resin film, and the thermosetting resin in the film contains one or more types selected from the group consisting of epoxy resins, allylated epoxy resins, allylated polyphenylene ether resins, phenolic resins, polyimide resins, polyamide resins, bismaleimide resins, maleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, polyester resins, silicone resins, and acrylic resins.

7. 3. The electromagnetic shielding film according to claim 2, wherein the impregnating resin is a thermoplastic resin, and the thermoplastic resin includes at least one selected from the group consisting of polyethylene, polypropylene, fluororesin, polyethylene terephthalate, polyethylene naphthalate, and polyimide.

8. 3. The electromagnetic wave shielding film according to claim 2, wherein the impregnating resin is a thermosetting resin, and the thermosetting resin comprises at least one selected from the group consisting of epoxy resins, allylated epoxy resins, allylated polyphenylene ether resins, phenolic resins, polyimide resins, polyamide resins, bismaleimide resins, maleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, polyester resins, silicone resins, and acrylic resins.

Citation Information

Patent Citations

  • Carbon-nano-tube-based electromagnetic shielding material and adhesive tape and manufacturing method of adhesive tape

    CN109628006A

  • Systems and methods for forming and harvesting nanofibrous materials

    JP2009509066A

  • Nanotube-based insulator

    JP2014508054A

  • Carbon nanotube sheet structure and manufacturing method thereof

    JP2017529298A

  • Coaxial cable using plated carbon nanotube elements and method of manufacture thereof - Patent Application 20070122997

    JP2021529421A